Drug Discovery and Development Strategies for COVID-19 - Shrestha, Aarajana; Kadayat, Tara Man (Europasian Journal of Medical Sciences, 2020)
Coronavirus Disease 2019 (COVID-19) has emerged as a global threat. Scientists and clinicians are endeavoring to find effective drugs and vaccines for this disease. This special issue of the Europasian Journal of Medical Sciences (EJMS) aims to cover the problems, solutions, and challenges of COVID-19 around the world. In this Editorial, EJMS Editors Aarajana Shrestha and Tara Man Kadayat highlight the processes of drug discovery and development and a brief overview of the current drug development strategies against COVID-19.